Respuesta :
This is an aritmetic series;
a=-10
d=-7--10
d=3
n= 7
Sum=[tex] \frac{n}{2} [/tex](2a+(n-1)d)
Sum=[tex] \frac{7}{2} (2*(-10)+(7-1)3)[/tex]
sum=3.5(-20+18)
sum=3.5(-2)
sum=-7
a=-10
d=-7--10
d=3
n= 7
Sum=[tex] \frac{n}{2} [/tex](2a+(n-1)d)
Sum=[tex] \frac{7}{2} (2*(-10)+(7-1)3)[/tex]
sum=3.5(-20+18)
sum=3.5(-2)
sum=-7
Answer:
d -7
Step-by-step explanation:
The sum of an arithmetic sequence Sn whose first and last terms are known may be expressed as
Sn = n/2(a + l)
where a and l are the first and last terms of the arithmetic sequence with n number of terms
Thus for the given sequence, the sum Sn is
S₇ = 7/2 (-10 + 8)
Since there are 7 terms in the sequence
= 3.5 * -2
= -7